Survey on Public Participation of Malaysia’s MRT Project with Reference To Environmental Impact Assessment - Zain, F. M.Y.; Omar, D. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Public participation plays a very important role to ensure the process of developing a country has support from the citizen as well as letting the citizen know on the development which might affect them later on. Public participation has been used in various matters and is widely known as a requirement in regulation, internationally and domestically. However, this paper focuses on the environmental impact assessment (EIA) process and it concentrates on public participation process in EIA. This study is carried out to identify why there is a need for improvement in public participation of EIA process. The study uses the MRT project in Malaysia as its case study. The study leads to identify the level of public understanding and level of public participation in EIA process.